Maslahat Layanan Go-Food Pada Industri Kuliner (Pendekatan Structure-Conduct-Performance) - Wahyudi, Heru; Sari, Ratna (Penerbit Goodwood, 2022)
Purpose: The aim of the research this is how the impact of service Go-Food to the structure , conduct and performance of businesses in the entrepreneur culinary stalls eat in Kampung Baru , Bandar Lampung. Research methodology: The data used are primary data, which is obtained from the results of distributing questionnaires which are the perceptions of the food stall entrepreneurs eat in Kampung Baru who join become partners Go-Food. Technique Capturing the sample that is used is total sampling, with samples of research throughout businessman stalls eat that up with Go-Food. This research uses descriptive quantitative method. This method aims to describe the phenomena that are related to the problem under study so that the resulting data is quantitative descriptive data Results: The results of the study have concluded that Go-Food has good impact to the structure , behavior , and performance of the business of culinary warun g eat in Kampung Baru.